Caracterização parcial de uma Ca2+ -ATPase de larva de Pachymerus nucleorum (Coleoptera: Chrysomelidae: Bruchinae) - Cruz, Gabriel Costa Nunes da (2006)
A high Ca2+-ATPase activity fraction was obtained from Pachymerus nucleorum larvae. The larvae were dissected in order to take off the digestive system. The remaining material was homogeneized in extraction buffer and centrifuged at 15000xg for 30 minutes. The resulting precipitate, fraction P1, was homogeneized in imidazole buffer containing Triton X-100 0.2%, incubated for 20 minutes at room temperature and centrifuged under the aforementioned conditions. The precipitate fraction P2 was homogeneized in imidazole buffer containing 50 mM pyrophosphate. After incubation for 20 minutes at room temperature, a centrifugation at 40000xg for 30 minutes was done. The precipitate fraction P3 was homogeneized in imidazole buffer and presented high Ca2+- ATPase activity that was characterized. The fraction P3 did not present significant ATPase activity in presence of some cations: magnesium, cobalt, cupper, zinc, barium, lithium or iron. The high Ca2+-ATPase activity was inhibited in presence of 4 mM cobalt, cupper, zinc, barium or iron. 0.25 mM magnesium caused 50% inhibition of this activity. In presence of 1 mM ATP the P3 ATPase activity gets 50% with 0.5 mM CaCl2, reaching a plateau with 2 mM. In presence of 1 mM 31 CaCl2 the ATPase activity gets 50% with 0.7 mM ATP and the pick with 2 mM. However we observed that there is a slight decline of this activity with ATP concentrations higher than 2 mM. P3 used neither pyrophosphate nor mono- or diphosphate nucleotides as substrate, and the Ca2+-GTPase activity is only 20% that of the Ca2+-ATPase. This fraction did not undergo significant inhibition by vanadate, in concentrations smaller than 200 µM, azide, Triton X-100 or aluminum fluoride. The K+/EDTA-ATPase activity was 50% of the Ca2+-ATPase and did not occur imunoreactivity with anti-myosin II or V antibodies. In this work we obtained a Ca2+-ATPase activity enriched fraction from Pachymerus nucleorum larvae lacking digestive system and partially characterized this activity.